Private Activity in Infrastructure in Europe and Central Asia Remained Stable in 2010 - Parulekar, Koustubh (World Bank, Washington, DC, 2012)
In 2010, 23 infrastructure projects with private participation reached financial or contractual closing in five low- and middle-income countries in Europe and Central Asia, involving investment commitments of US$14.8 billion. Infrastructure projects implemented in the 1990-2009 period attracted new investment of US$12.8 billion, bringing total investment commitments to infrastructure sectors to US$27.6 billion in 2010. Public Private Infrastructure (PPI) activity was also concentrated on green field projects, which accounted for 12 of the 23 new projects and attracted 74 percent of regional investment in 2010.